The use of metal alloys in the manufacture of fixed prosthetic restorations - Gabriel Ciochinda; Mihai Augustin; Gabriela Tanase (Amaltea Medical Publishing House, 2022)
The techniques and classical methods used to make fixed prosthetic restorations may involve recycled metal alloys from previous castings. The article presents an assessment of the procedures that dental technicians apply, the principles and criteria that are at the base of their choices and decisions when they use metal alloys in fixed prosthetic restorations. Objective. The article aims at the identification of the practices used by dental technicians in Romania when manufacturing non-noble metal alloys prosthetic suprastructures. Material and method. The data collection methodology is an attribute of both quantitative and qualitative research. Results. Over 50% of the dental laboratories are using classical methods of processing metal alloys, 82% of dental technicians use non-noble alloys (Cr-Ni, Cr-Co). 60.7% apply the recycling technique by reusing alloys and 46.4% of them are reusing the materials. Defining factors for choosing recycling process are determined on "personal appreciation based on experience in the field" and "financial-economic" criteria. Discussions. Scientific studies investigating the negative effects of recycling processes used for fixed prosthetic suprastructures emphasize on microstructural and chemical changes, consequences on the mechanical strength of the materials. They underline the strength in acidic environment, significant long-term toxic contribution in relation to the acidic environment of the oral cavity. Conclusions. The predominant use of classical laboratory methods favours the over - reuse of alloys left overs from previous melts as well as materials. The effects of these techniques are drastic and the cautious use is fundamental.